PENGARUH BRAND IMAGE PRODUK EIGER TERHADAP LOYALITAS PELANGGAN PADA ANGGOTA MAPALA PERGURUAN TINGGI DI SURABAYA - Fauzira, Iza; Wahyuni, Jauhar (Universitas Negeri Surabaya, 2025)
Brand image is the way customers perceive a brand. A good image created by the company can provide satisfaction to customers so that customer loyalty is formed. Eiger products are one of the outdoor products that have a fairly good image among the community, one of which is in the environment of Higher Education Nature Lovers in Surabaya. Eiger's outdoor products have become one of the choices of outdoor products used during outdoor activities. This study aims to determine the effect of Eiger product brand image on customer loyalty among college mapala members in Surabaya. This research is an associative quantitative research with survey method. The results of this study indicate that the brand image of Eiger products has a positive and significant influence on customer loyalty. The effect has a percentage of 48.6% so that it has created a considerable impact in seeing the influence of Eiger's brand image to customer loyalty in mapala members in Surabaya universities.